2018
DOI: 10.1074/mcp.ra117.000533
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomic and Proteomic Analyses Suggest the Participation of Endogenous Protease Inhibitors in the Regulation of Protease Gene Expression in Helicoverpa armigera

Abstract: Insects adapt to plant protease inhibitors (PIs) present in their diet by differentially regulating multiple digestive proteases. However, mechanisms regulating protease gene expression in insects are largely enigmatic. Ingestion of multi-domain recombinant protease inhibitor-7 (CanPI-7) arrests growth and development of (Lepidoptera: Noctuidae). Using RNA sequencing and proteomic analysis, we examined the response of larvae fed on recombinant CanPI-7 at different time intervals. Here, we present evidence supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Similar results were found for trypsins and chymotrypsins, which showed individual members of each family being up to > 25 fold up or downregulated depending on the gene in question. A similar transcription pattern in trypsins and chymotrypsins was previously [ 31 ] found following feeding with protein inhibitors. While not a primary focus of this study, a more detailed functional investigation of these digestive enzymes would be useful in order to ascertain whether these changes are adaptive.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were found for trypsins and chymotrypsins, which showed individual members of each family being up to > 25 fold up or downregulated depending on the gene in question. A similar transcription pattern in trypsins and chymotrypsins was previously [ 31 ] found following feeding with protein inhibitors. While not a primary focus of this study, a more detailed functional investigation of these digestive enzymes would be useful in order to ascertain whether these changes are adaptive.…”
Section: Resultssupporting
confidence: 84%
“…GO term overrepresentation analysis (Table S6) showed that genes commonly overexpressed in the midgut of all larval stages are related to digestive functions such as lipid metabolism (GO:0006629) and proteolysis (GO:0006508). This finding was also observed in the stink bug N. viridula, and is commonplace among insects as it has been proven that they play an important role in the breakdown of proteins in the ingested food [17,30,31].…”
Section: Comparisons Across Larval Stages Suggest Conserved Regulatio...supporting
confidence: 62%
“…Serine like proteinases expressed in early stages of larval growth is predominantly sensitive to PIs than the once expressed in the later stages of growth. Therefore, the larval growth and mortality rates depend on the stage of the larval growth and the effectiveness of the PIs resulting in delay of mortality rate of H. armigera (Bhattacharjee et al, 2010;Lomate et al, 2018;Chikate et al, 2013). These findings indicated that ingestion of transgenic leaves expressing ChTI at early stages of larval growth could control the lepidopteran population effectively.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, serine protease was the main protease class expressed in the fifth instar. High cysteine protease activities have already been detected in studies involving young larvae of Lepidoptera (Liu et al, ; Senthil‐Nathan, ) as well as the control of the gene expression of these enzymes, showing that there is an increase in the synthesis of serine proteases rather than the decrease of cysteine proteases in Tribolium castaneum (Lomate et al, ).…”
Section: Resultsmentioning
confidence: 95%